(untitled) (Journal of Economic Research & Business Administration, 2015)
Prospects for achieving the strategic objectives of improving the competitiveness of the Kyrgyz economy and its prosperity is based on the development of innovation sphere. At the present stage industrialized countries are experiencing a transition to an innovation economy, which is based on an effective system for developing and implementing new technology solutions in various spheres of activity. This article describes the formation of new, innovative outlines, which are determined mainly by the economic environment.